Possible binding sites and interactions of propanidid and AZD3043 within the γ-aminobutyric acid type A receptor (GABAAR). Issue 15 (18th November 2018) - Wang, Shanshan; Liu, Qingzhu; Li, Xi; Zhao, Xueyu; Qiu, Ling; Lin, Jianguo
Abstract : Propanidid is an intravenous anesthetic with transient action and rapid recovery features, but it is clinically unacceptable due to its side effects. AZD-3043, an analog of propanidid with the methoxy group substituted by the ethoxy group, has become the focus of recent development efforts. Although propanidid and AZD-3043 are known to act by potentiating the γ-aminobutyric acid type A receptors (GABAA Rs), their action sites and binding modes in the recognition of target proteins still remain unclear. In this study, molecular docking and ONIOM calculations were performed to explore the possible binding sites and binding modes of propanidid and AZD-3043 with the GABAA R. The predicted active region located in the transmembrane domain (TMD) of GABAA R was identified as the most favorable binding site for propanidid and AZD-3043, with the highest docking score (−39.69 and −39.44 kcal/mol, respectively) and the largest binding energy (−88.478 and −78.439 kcal/mol, respectively). The important role of amino acids Asp245, Asp424, Asp425, Arg428, Phe307, and Ser308 in determining the binding modes of propanidid or AZD-3043 with GABAA R was revealed. The detailed molecular interactions between propanidid and AZD-3043 and the GABAA R were revealed for the first time. This could improve our understanding of the action mechanism of general anesthetics and will be helpful for the design of more potential lead-like molecules.